Rural Bank Technical Efficiency in West Java Indonesia: Evaluation by Ownership and District - Mokhamad Anwar; Layyinaturrobaniyah Layyinaturrobaniyah; Ratna Komara; Sulaeman Rahman Nidar (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2018)
This study examines the efficiency of rural banks in West Java Indonesia in terms of technical efficiency. The analysis covers the 212 banks spread over some districts in west java province during the period 2012-2016. Those banks are under the supervision of the Financial Services Authority Regional Office of Bandung. The study employs Data Envelopment Analysis to obtain the technical efficiency of the banks over the study period. The study results suggest that there are some rural banks from certain districts enjoying most efficient; average efficiency of those banks over the study period is inclined to increase with the peak performance occurred in 2015. The other findings suggested that capital adequacy and bank size are of essential factors determining rural bank efficiency in West Java.